The Implementation of Ice Breaking in Improving the Spirit of Learning Children of Group B in Dharma Wanita Persatuan Lambangan Kindergarten, Wonoayu - Lestari, Yulinda Widya; Dwijo, Al Qudus Nofiandri Eko Sucipto; Widyaningrum, Siska; Musyarofah, Anis (Universitas Nahdlatul Ulama Surabaya, 2021)
This research aimed at knowing whether the implementation of ice breaking activities can increase the enthusiasm of early childhood learning in Dharma Wanita Persatuan Lambangan Kindergarten. This research was conducted at Dharma Wanita Persatuan Lambangan, Wonoayu. This research uses classroom action research using the observation method. The subjects in this classroom action research were students in group B of Dharma Wanita Persatuan Lambangan Wonoayu Kindergarten, which consisted of 18 children (4 boys and 14 girls). The object of this research is the implementation of ice breaking in increasing children's enthusiasm for learning. the results of this study in the first cycle showed that out of 18 students, there were no children who were in the very high category. The percentage results from the first cycle of action were 37.04% in the high and medium categories, and 62.96% of the children entered in the low category. The results obtained in the second cycle showed that of the 18 students, there were no students whose learning enthusiasm was very low, the percentage obtained from the second cycle of actions showed very high, high and medium categories reaching 94.44% while those in the low category had the smaller percentage is 5.56%. So this study shows that the implementation of ice breaking activities can increase the learning spirit of group B children in Dharma Wanita Persatuan Lambangan Kindergarten because each child has achieved the criteria and managed to achieve at least 80% completeness in the high success category. and very high in cycle II.